Sex Modulates Lactobacillus johnsonii N6.2 and Phytophenol Effectiveness in Reducing High Fat Diet Induced mTOR Activation in Sprague-Dawley Rats - Kling, Danielle N.; DeBose-Scarlett, Evon M.; Teixeira, Leandro D.; Gezan, Salvador A.; Lorca, Graciela L.; Gonzalez, Claudio F. (Frontiers in Microbiology, 2018)
Metabolic syndrome (MetS) is the underlying cause of some devastating diseases, including type 2 diabetes and cardiovascular disease. These diseases have been associated with over-activation of the mechanistic Target of Rapamycin (mTOR) pathway. This study utilizes a high fat diet (HFD) to induce MetS and to dissect the effects of a beneficial bacterium, L. johnsonii N6.2, and natural phenolics on mTOR complex 1 (mTORC1) expression compared to a reduced energy density diet (REDD). HFD significantly elevated MetS markers in males, as noted through an increase in weight, glucose levels, and triglyceride levels. Treatments were effective in reducing mTORC1-activating phosphorylations of pAKT-T308 and pAKT-S473 (p = 0.0012 and 0.0049, respectively) in HFD-fed females, with the combined treatments of L. johnsonii and phytophenols reducing phosphorylations below REDD-fed control levels, and significantly below HFD-fed control levels. Meanwhile, diet was the significant factor influencing male mTORC1-activating phosphorylations (p < 0.0001), as treatments were only effective in reducing these phosphorylations in REDD-fed animals. Downstream analysis of mTORC1 activated genes phosphogluconate dehydrogenase (pgd) and phosphofructose kinase (pfk) followed this similar trend, enforcing the significant effect sex has on a treatments’ ability to modulate diet induced abnormalities. Analyzing mTORC1 stimulators such as insulin, inflammatory cytokines, and tryptophan, revealed no significant differences among groups. These results indicate that the effects observed on mTORC1 are a direct consequence of the treatments, and not exerted indirectly via the modulation of stimuli. This study highlights the potential use of the microbiome and natural compounds in reducing the onset of metabolic diseases through mTORC1.